MEASUREMENT ERROR IN COORDINATE MEASURING MACHINES - Квасніков, В. П.; Петров, А. А. (Science-based technologies, 2009)
In this article is considered the contactless way of the control of geometrical parameters of surfaces of details. Precision of the given method depends on presence of noise. The control of roughness of a urface is provided with dependence of intensity of dispersion of light at its reflection from microroughnesses of a surface. Than more are microroughnesses, more is dispersion of light. The analysis of the received data and comparison of the received results with a margin error is provided with use of different methods with the mathematical description of distributions which characterize sensitivity of the measuring device and influence of noise.